An Optimal approach of Emotion Detection Using Deep Learning - Singh, Priti; Sharan, Hari Om; Raghuvanshi, C. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Smart facial emotion detection is a fascinating field of research that has been presented and implemented in several fields, including defense, health, and human-machine interfaces. Researchers in this area are focusing on strategies to encrypt, decode and erase facial expressions to enhance algorithm prediction. Various deep learning algorithms and cognitive internet of thing (CIoT) are being used to improve efficiency due to the exponential development of this technology. The aim of this work is to provide a summary of recent work on smart facial expression recognition using deep learning Algorithm and define new approach of emotion detection. Due to the exponential growth of the Internet of Things, current internet of thing-based technologies around automated intelligent services lacks technological resources, meaning that they would be unable to meet the needs of industrial services. The incremental enrichment of internet of thing technology for smart environments has resulted in technology delays and decreased market productivity. Deep learning is one of the most used machine learning techniques in a variety of applications and experiments. Designing an emotional intelligent approach and deep learning that will inspire internet of thing is a pressing need to solve this problem, according to Recent Application in facial Emotion detection.